Nursing Research Priorities in Critical Care, Pulmonary, and Sleep: International Delphi Survey of Nurses, Patients, and Caregivers: An Official American Thoracic Society Workshop Report - George, Maureen (Ann Am Thorac Soc, 2020)
The objective of this workshop was to determine current nursing research priorities in critical care, adult pulmonary, and sleep conditions through input from consumer (patient, family, and formal and informal caregivers) and nursing experts around the world. Working groups composed of nurses and patients selected potential research priorities based on patient insight and a literature review of patient-reported outcomes, patient-reported experiences, and processes and clinical outcomes in the focal areas. A Delphi consensus approach, using a qualitative survey method to elicit expert opinion from nurses and consumers was conducted. Two rounds of online surveys available in English, Spanish, and Chinese were completed. A 75% or greater threshold for endorsement (combined responses from nursing and consumer participants) was determined a priori to retain survey items. A total of 837 participants (649 nurses and 188 patients, family, and/or caregivers) from 45 countries responded. Survey data were analyzed and nursing research priorities that comprise 23 critical care, 45 adult pulmonary, and 16 sleep items were identified. This project was successful in engaging a wide variety of nursing and consumer experts, applying a patient-reported outcome/patient-reported experience framework for organizing and understanding research priorities. The project outcome was a research agenda to inform, guide, and aid nurse scientists, educators, and providers, and to advise agencies that provide research and program funding in these fields.